A Contralateral Eye Study Comparing Apodized Diffrative and Full Diffrative Lenses: Wavefront Analysis and Distance and Near Uncorrected Visual Acuity - Marcony R. Santhiago; Marcelo V. Netto; Jackson Barreto; Beatriz de Abreu Fiúza Gomes; A. R. Schaefer; Newton Kara-Júnior (2009)
To evaluate intraindividual visual acuity, wavefront errors and modulation transfer functions in patients implanted with two diffractive multifocal intraocular lenses. This prospective study examined 40 eyes of 20 cataract patients who underwent phacoemulsification and implantation of a spherical multifocal ReSTOR intraocular lens in one eye and an aspheric Tecnis ZM900 multifocal intraocular lens in the other eye. The main outcome measures, over a 3-month follow-up period, were the uncorrected photopic distance and near visual acuity and the defocus curve. The visual acuity was converted to logMAR for statistical analysis and is presented in decimal scale. The wavefront error and modulation transfer function were also evaluated in both groups. At the 3-month postoperative visit, the mean photopic distance uncorrected visual acuity (UCVA) was 0.74 ± 0.20 in the ReSTOR group and 0.76 ± 0.22 in the Tecnis group (p=0.286). The mean near UCVA was 0.96 ± 0.10 in the ReSTOR group and 0.93 ± 0.14 in the Tecnis group (p=0.963). The binocular defocus curve showed measurements between the peaks better than 0.2 logMAR. The total aberration, higher-order aberration and coma aberration were not significantly different between the groups. The spherical aberration was significantly lower in the Tecnis group than in the ReSTOR group. (p=0.004). Both groups performed similarly for the modulation transfer function. The ReSTOR SN60D3 and Tecnis ZM 900 intraocular lenses provided similar photopic visual acuity at distance and near. The diffractive intraocular lenses studied provided a low value of coma and spherical aberrations, with the Tecnis intraocular lens having a statistically lower spherical aberration compared to the ReSTOR intraocular lens. In the 5 mm pupil diameter analyses, both intraocular lens groups showed similar modulation transfer functions.